2016
DOI: 10.2215/cjn.07110615
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Glucocorticoids or Calcineurin Inhibitors in Primary FSGS

Abstract: Background and objectives In primary FSGS, calcineurin inhibitors have primarily been studied in patients deemed resistant to glucocorticoid therapy. Few data are available about their use early in the treatment of FSGS. We sought to estimate the association between choice of therapy and ESRD in primary FSGS.Design, setting, participants, & measurements We used an inception cohort of patients diagnosed with primary FSGS by kidney biopsy between 1980 and 2012. Factors associated with initiation of therapy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
1
42
0
1
Order By: Relevance
“…Such prolonged high-dose steroid course has substantial toxicity and significant morbidity. Nevertheless, a recent retrospective case series from the University of North Carolina suggested more favorable outcomes, with a hazard ratio for renal survival of 0.49 (95% CI 0.28-0.86) in subjects with FSGS who received high-dose glucocorticoid therapy for a median of 3.0 months (interquartile range [IQR] 1.5-5.9 months) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Such prolonged high-dose steroid course has substantial toxicity and significant morbidity. Nevertheless, a recent retrospective case series from the University of North Carolina suggested more favorable outcomes, with a hazard ratio for renal survival of 0.49 (95% CI 0.28-0.86) in subjects with FSGS who received high-dose glucocorticoid therapy for a median of 3.0 months (interquartile range [IQR] 1.5-5.9 months) [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the Clinical Journal of the American Society of Nephrology, Laurin et al (19) present an analysis of the largest cohort of patients with idiopathic FSGS to date. Using the Glomerular Disease Collaborative Network (GDCN) Registry, Laurin et al (19) showed that early treatment with any immunosuppression was associated with significantly greater renal survival compared with no immunosuppression in 458 adults and children with FSGS (hazard ratio, 0.49 for ESRD; 95% confidence interval [95% CI], 0.28 to 0.86).…”
mentioning
confidence: 99%
“…Using the Glomerular Disease Collaborative Network (GDCN) Registry, Laurin et al (19) showed that early treatment with any immunosuppression was associated with significantly greater renal survival compared with no immunosuppression in 458 adults and children with FSGS (hazard ratio, 0.49 for ESRD; 95% confidence interval [95% CI], 0.28 to 0.86). There was no significant difference in renal survival among patients treated with glucocorticoids alone compared with patients treated with CNIs, although there was a trend toward greater survival among patients treated with CNIs.…”
mentioning
confidence: 99%
See 2 more Smart Citations